Da Lei nº 13.415/2017 ao Referencial Curricular Gaúcho do Novo Ensino Médio: processos de recontextualização - Centenaro, Junior Bufon (2023)
The following thesis aimed to comprehend the recontextualization process in the development of the Rio Grande do Sul State Curriculum for High School (RCG-EM) and the shifts in meaning generated concerning the discourse of national official devices for the New High School (NEM). The research problem was guided by the following question: What shifts in meaning are evident in relation to the national official statements of the NEM in the recontextualizing movement that produced the RCG-EM? The theoretical framework adopted was based on the contributions of Basil Bernstein's theory of the pedagogic device (1996; 1998) and his concept of recontextualization. Bernstein's studies have been employed in the analysis of curricular policies, especially based on the understanding of the shifts that texts and discourses undergo when circulating between governmental contexts and instances and, from these, to schools. This application has been confirmed by the research of Morais and Neves (2001; 2007), Silva (2008; 2014), Mainardes (2006), Mainardes and Stremel (2010), Silva (2010), Lopes and Macedo (2011), Silveira, Silva, and Oliveira (2022), Oliveira and Silva (2023), which constitute fundamental theoretical references for the thesis regarding the analytical perspective of curricular policy recontextualization. The analytical-hermeneutic method was employed, involving categorization, coding, ordering, and regrouping of data and information, as well as descriptive and reflective analyses of the investigated field, while adopting a hermeneutic stance through the circular relationship between the researcher and the investigated object/field. Data production procedures included literature review, document analysis, and semi-structured interviews with teachers who contributed to the RCG-EM. The research was guided by the following hypotheses: (i) despite explicit national guidelines on how to write and implement the state curriculum, such information and guidance, when received, are reinterpreted based on the culture and biography of the actors; (ii) developing a curricular document at the state level from national-level devices requires interpretation, permeated by consensus and dissensus regarding meanings and significances, making the construction of the curricular text a unique creative process in each locality; (iii) although recontextualization is inevitable, it can vary, as depending on how the process occurs, it can produce a curricular text very similar but also present a result quite different from the one it started with. Among the main results of the research were the following: (i) the conception of the teacher in the RCG-EM as the curriculum author, knowledge producer, and subject of praxis differed from that identified in the national official discourse of the NEM, which defines the teacher as an adaptable and standardized subject unilaterally aligned with the curriculum by skills and competencies; (ii) the RCG-EM did not exclude the construction of the Pedagogical Political Project, unlike the national official discourse of the NEM; (iii) the life project approach in the RCG-EM sought to overcome a narrow vision focused only on reducing it to entrepreneurship; (iv) it was found that the Reference did not omit issues such as gender equality, overcoming sexism, racism, homophobia, and other forms of prejudice and violence, practically absent in the national official documents that structured the high school reform. However, the evidenced results did not represent a rupture or transformation in relation to this reform. As a general conclusion, it is asserted that the essence of the NEM was maintained, considering that the process of developing the RCG-EM did not manage to increase the workload of basic general education or change the profound problem of formative itineraries. Thus, it can be said that there were not proper shifts in meaning, but hybridizations and additions of meanings that, despite their relevance, did not modify the core of the NEM, deeply dualistic and imprisoned by neoliberal interests